Pengaruh Insentif, Motivasi Dan Penilaian Prestasi Terhadap Kinerja Karyawan Pada PT. Young-Il Indonesia - Pallawagau, Andi; Asyari; Yolanda, Olivia (CV ODIS, 2023)
This research aims to examine the relationship between incentive, motivation, and achievement assessment variables on employee performance. Performance measurement is seen based on employee output by looking at the targets and production set by management. Employee behavior is dynamic and will change according to comfort, expectations, and the company environment. Systematic performance assessment to evaluate the effectiveness, competence, and skills of the work as well as the benefits for the company. The research analysis unit was carried out at PT. Young-il Indonesia. The research method is based on the results of a questionnaire analyzed quantitatively statistically with the help of SPSS 25. The population and sample of employees from all companies totaling 80 employees using hypothesis testing linear regression testing and goodness of fit test (R Square test). The research results show that the incentive variable has a significant positive effect on employee performance. Motivation has a significant positive effect on employee performance. Achievement appraisal has a significant positive effect on employee performance